Historical Sex Work : New Contributions from History and Archaeology - Munns, Anna M.; Smith, Angela J. (Angela Joan); Fellows, Kristen R. (Book collections on Project MUSE., 2020)
"Exploring the sex trade in America from 1850 to 1920 through perspectives from archaeologists and historians, this volume expands the geographic and thematic scope of research on the subject, helping create an inclusive and nuanced view of social relations in United States history"--